2015
DOI: 10.1063/1.4918490
|View full text |Cite
|
Sign up to set email alerts
|

Rapid control of mold temperature during injection molding process

Abstract: Effect of fast mold surface temperature evolution on iPP part morphology gradients AIP Conference Proceedings 1713, 170001 (2016) Abstract. The control of mold surface temperature is an important factor that determines surface morphology and its dimension in thickness direction. It can also affect the frozen molecular orientation and the mold surface replicability in injection molded products. In this work, thin thermally active films were used to quickly control the mold surface temperature. In particular, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…To obtain a smooth surface, the specimens were microtomed by a Leica microtome. The specimens were then chemically etched following the procedure reported by White and Bassett [53] and previously adopted on similar iPP samples [37,38,42]. In order to determine the effect of the etching procedure on the mechanical results, the samples were etched for different times.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain a smooth surface, the specimens were microtomed by a Leica microtome. The specimens were then chemically etched following the procedure reported by White and Bassett [53] and previously adopted on similar iPP samples [37,38,42]. In order to determine the effect of the etching procedure on the mechanical results, the samples were etched for different times.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In this paper, we intend to demonstrate the applicability of HarmoniX AFM technique to the characterization of molded polymer samples with complex, nonuniform morphologies [37][38][39][40][41][42], which could influence the mechanical properties of the final object [28,43,44]. To accomplish this objective, a series of HarmoniX tests have been performed on selected polypropylene molded samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating device is composed by a conductive layer, that is electrically insulated from the mold by two polyimide layers, and a steel layer (100 micron thickness) covers that device and comes in contact with the polymer [5].…”
Section: Materials and Molding Experimentsmentioning
confidence: 99%
“…On the other hand, setting a high mold temperature addition cooling time is required. Previous works [4][5][6] demonstrated that it is possible to obtain a fast temperature evolution on the mold surface in order to have a high mold temperature only during the filling and a fast cooling soon after. Temperature evolution on mold surface has a significant effect on the morphology distribution of the final object [7,8].…”
Section: Introductionmentioning
confidence: 99%